2018
DOI: 10.1177/0310057x1804600404
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Hyperthermia during Craniotomy

Abstract: There is evidence that even mild hyperthermia may exacerbate brain injury. There seem reasonable grounds for considering patients undergoing craniotomy as 'at risk' for brain injury. A retrospective observational study was undertaken to measure the incidence of mild hyperthermia in craniotomy cases in which the patient was initially normothermic. Auckland City Hospital's database of electronic anaesthetic records was searched for adult patients who were normothermic (≤37°C) prior to undergoing craniotomy proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Если этот методический подход является реально рабочим, а так, по-видимому, и есть, то перспективы для этой методики церебральной термометрии открываются колоссальные. Но, конечно, основное поле для деятельности не анестезиология (хотя в недавней публикации Malpas et al [6] частота спонтанной гипертермии во время краниотомии составила 33,5 %), а интенсивная терапия пациентов с тяжелыми церебральными катастрофами [4,[7][8][9][10].…”
Section: ■■■unclassified
“…Если этот методический подход является реально рабочим, а так, по-видимому, и есть, то перспективы для этой методики церебральной термометрии открываются колоссальные. Но, конечно, основное поле для деятельности не анестезиология (хотя в недавней публикации Malpas et al [6] частота спонтанной гипертермии во время краниотомии составила 33,5 %), а интенсивная терапия пациентов с тяжелыми церебральными катастрофами [4,[7][8][9][10].…”
Section: ■■■unclassified
“…22 Another small (n = 107) prospective non-randomized study in colorectal surgery patients and also found no significant difference in the incidence of perioperative hypothermia. 23,24 There was no significant difference in perioperative temperature profiles between open and laparoscopic (minimally invasive) surgery in a review of 45 casecontrolled anaesthetics, 26 and the incidence of hypothermia in colorectal surgery was 74% (n = 255) with no significant difference between open and laparoscopic surgery. 25 A weakness of the aforementioned studies is relatively small size.…”
Section: Introductionmentioning
confidence: 99%
“…A weakness of the aforementioned studies is relatively small size. Anaesthesia information management systems (AIMS) allow for continuous recording and audit of patient temperature profiles 26 . The aim of this study was to compare the perioperative temperature profile of patients undergoing open and laparoscopic colorectal surgery to define the incidence and severity of IPH, and to compare these two surgical approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation